2016
DOI: 10.1007/s12325-016-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Intraocular Pressure Reduction of Travoprost Ophthalmic Solution in Subjects with Normal Tension Glaucoma

Abstract: IntroductionWe examined the sustainability of the intraocular pressure (IOP)-lowering efficacy of travoprost (0.004%) ophthalmic solution in subjects with normal tension glaucoma (NTG).MethodsTravoprost ophthalmic solution was given once daily at 9 PM to subjects with newly diagnosed NTG or with NTG who had not received any ocular hypotensives within the previous 30 days. IOP was measured at three time points (9 AM, 1 PM, and 5 PM) at baseline and week 12 visits, and at one time point (9 AM) at week 4 and week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Although the drug treatment period and the races varied between the ROCK inhibitor trials, sovesudil evidently showed lower rates of conjunctival hyperaemia, specifically 17.5% (7/ 40 subjects in low-dose group) and 24.4% (10/41 subjects in high-dose group). Additionally, the ocular AEs in this present trial are comparable to those of similar studies on b-blockers and PGA drugs with NTG patients (Tsumura et al 2012;Naito et al 2016). The dropout rate in the current study was relatively low, at ~8.4% (10/ 119 patients), with only 5 patients dropping out due to adverse ocular events (classified as mild or moderate).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although the drug treatment period and the races varied between the ROCK inhibitor trials, sovesudil evidently showed lower rates of conjunctival hyperaemia, specifically 17.5% (7/ 40 subjects in low-dose group) and 24.4% (10/41 subjects in high-dose group). Additionally, the ocular AEs in this present trial are comparable to those of similar studies on b-blockers and PGA drugs with NTG patients (Tsumura et al 2012;Naito et al 2016). The dropout rate in the current study was relatively low, at ~8.4% (10/ 119 patients), with only 5 patients dropping out due to adverse ocular events (classified as mild or moderate).…”
Section: Discussionsupporting
confidence: 79%
“…2012; Naito et al. 2016). The dropout rate in the current study was relatively low, at ~8.4% (10/119 patients), with only 5 patients dropping out due to adverse ocular events (classified as mild or moderate).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven articles were included in the final analysis (11 articles in Category 1 and 25 articles in Category 2; Figure 1 ). In Category 1, there were three articles for latanoprost, 15 – 17 two articles for travoprost, 18 , 19 one article for bimatoprost, 20 five articles for tafluprost 21 – 25 ( Table 1 ), and 0 articles for unoprostone. In Category 2, the number of articles for each PGA was as follows: 14 for latanoprost, 15 , 16 , 26 37 seven for travoprost, 18 , 19 , 26 , 38 – 41 three for bimatoprost, 20 , 26 , 40 seven for tafluprost, 21 – 23 , 25 , 26 , 39 , 40 and 0 articles for unoprostone ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%